Association between the triglyceride-glucose index and hyperuricemia: potential role of obesity in patients with Type 2 diabetes mellitus - Tang, Dou; Gu, Xi; Xuan, Yan; Zhu, Fanfan; Shen, Ying; Lu, Leiqun (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index has recently emerged as a simple surrogate marker of insulin resistance. However, the relationships among the TyG index, obesity, and hyperuricemia in individuals with T2DM remain unclear. This study investigates the associations of the TyG index and obesity with hyperuricemia in T2DM, and the possible role of obesity in these associations.MethodsIn this cross-sectional study, 1,159 adults with T2DM were enrolled. The TyG index was calculated as ln [fasting triglyceride (mg/dl) × fasting plasma glucose (mg/dl)/2]. Participants were stratified into hyperuricemia and non-hyperuricemia groups based on serum uric acid levels. Multivariable logistic regression and subgroup analyses were performed to assess the association between the TyG index and hyperuricemia. Mediation analysis quantified BMI’s contribution to this relationship.ResultsThe prevalence of hyperuricemia was 30.7%. After adjustment for age, gender, HbA1c, diabetes duration, eGFR, HDL-C, LDL-C, hypertension, hyperlipidemia, coronary heart disease, smoking status, and alcohol consumption, each unit increase in the TyG index was independently associated with a 36% elevated risk of hyperuricemia (OR = 1.36, 95% CI: 1.10-1.68). Subgroup analyses showed consistent associations across different patient subgroups. Mediation analysis indicated that BMI accounted for 20.0% of the relationship.ConclusionsThe TyG index and BMI were both associated with hyperuricemia in Chinese patients with T2DM, with BMI potentially representing an indirect link.